1978
DOI: 10.2149/tmh1973.6.167
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Schistosomiasis in the Taveta Area of Kenya, East Africa

Abstract: Abstract:A total of 963 individuals in three villages were examined for schistosomiasis by both skin test and schistosome ova detection in stool and urine in 1974. The antigen used for skin test was VBS adult S. japonicum antigen (1 : 10,000 dilution). Stool and urine samples were examined through the concentration methods. Egg-positive rate was 62.2 per cent in Jipe, 68.0 per cent in Eldoro, 69.6 per cent in Kivalwa. Jipe was infested mostly by S. mansoni, Kivalwa by S. haematobium and Eldoro by both two schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1978
1978

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Kilimanjaro. Katamine et al (1978) studied in detail the prevalence of schistosomiasis in some villages in this area and demonstrated that there are a village where S. mansoni is highly endemic, two villages where S. haematobium is highly endemic, a village where both the two schistosomes are endemic and a village where schistosome infection is rare. The same authors suggested that the fact mentioned above would be mainly influenced by the distribution of host snails of schistosomiasis in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Kilimanjaro. Katamine et al (1978) studied in detail the prevalence of schistosomiasis in some villages in this area and demonstrated that there are a village where S. mansoni is highly endemic, two villages where S. haematobium is highly endemic, a village where both the two schistosomes are endemic and a village where schistosome infection is rare. The same authors suggested that the fact mentioned above would be mainly influenced by the distribution of host snails of schistosomiasis in this area.…”
Section: Introductionmentioning
confidence: 99%